THE ONLINE LISTENING STRATEGY INSTRUCTION AND VOCABULARY KNOWLEDGE ON LISTENING SKILL OF GRADE 12 JAPANESE LANGUAGE LEARNERS IN BEKASI WEST JAVA - Fitri Astar; Yumna Rasyid; Siti Ansoriyah (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2021)
ABSTRACT This article presents the result of empirical research that investigates the effect of online listening strategies instruction and vocabulary knowledge on Japanese language learners' listening skill. Listening strategies instruction used are the integrative model and the Oxford model. Participants in the study were 44 Japanese language learners of grade 12 from SMAN 21 Bekasi. This research used a quantitative approach and a quasi-experimental method. The data was collected by pre-test and post-test related to the learners’ Japanese listening skills. The learners' vocabulary knowledge was also measured using a vocabulary knowledge test. The result showed that the online listening strategy instruction, integrative model could not be given to students of class XII of SMAN 21 Bekasi due to the absence of a significant effect of the method and vocabulary knowledge on listening skills of Japanese language learners of grade 12 from SMAN 21 Bekasi. The research shows the possibility of other factors such as learning independency and learner autonomy that can affect the effectiveness of online listening strategy instruction, integrative model on Japanese listening skills. Keywords: Listening Strategy Instruction; Listening Skill; Vocabulary Knowledge; Japanese language.